Robert Wilmot Horton and liberal Toryism - Lamont, Stephen Peter (2015)
This thesis examines aspects of the political career of Robert Wilmot Horton (1784-1841), a junior minister in the Tory governments of the 1820s and an advocate of state-aided emigration to the British colonies. It considers how far Wilmot conforms to existing conceptualisations of 'liberal Toryism', which are summarized in Chapter 1.